1999
DOI: 10.1159/000016552
|View full text |Cite
|
Sign up to set email alerts
|

Fingernail Fluoride: A Method for Monitoring Fluoride Exposure

Abstract: This work was based on the hypothesis that fingernail clippings can be used as a biomarker for the subchronic exposure to fluoride. The results provide data on factors that may affect the concentration of fluoride in fingernail clippings as determined with the electrode following HMDS–facilitated diffusion. The following variables had only minor or no effects on the concentrations: (1) the surface area of the clippings (intact, minced or filed into powder) that were placed into the diffusion dishes; (2) soakin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
69
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 6 publications
9
69
1
1
Order By: Relevance
“…However, the data suggesting that fingernails could be a biomarker of F exposure from drinking water give support to limitations of using fingernails as F exposure from dentifrice. Whitford et al (7) showed that F concentration in fingernails of children living in fluoridated areas with 1.6 and 2.3 ppm F was significantly higher than in children living in non-fluoridated areas (p<0.0001). Nevertheless, the difference between those subjected to water containing 1.6 and 2.3 ppm F showed, by the 95% confidence interval, an overlap between the data.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the data suggesting that fingernails could be a biomarker of F exposure from drinking water give support to limitations of using fingernails as F exposure from dentifrice. Whitford et al (7) showed that F concentration in fingernails of children living in fluoridated areas with 1.6 and 2.3 ppm F was significantly higher than in children living in non-fluoridated areas (p<0.0001). Nevertheless, the difference between those subjected to water containing 1.6 and 2.3 ppm F showed, by the 95% confidence interval, an overlap between the data.…”
Section: Discussionmentioning
confidence: 98%
“…However, promising findings have been found when children living in communities with 1.6 or 2.3 ppm F in drinking water were shown to present significantly higher F concentrations in fingernails than populations living in communities with non-fluoridated water (7). Although the authors…”
Section: Introductionmentioning
confidence: 94%
“…An additional daily intake of 3.0 or 1.8 mg fluoride over 30 days in both men and women resulted three months later in an increase of the fluoride content of fingernails, and with some further delay also of toenails (Whitford et al, 1999b). Subjects living in areas with a high fluoride concentration in water (1.6-3.1 mg/L) had 1.8 and 2.9 times higher fluoride concentrations in fingernails than subjects from areas with intermediate (0.5-1.1 mg/L) or low (< 0.11 mg/L) fluoride concentration in water, respectively (Schamschula et al, 1985).…”
Section: Nailsmentioning
confidence: 99%
“…There is no clear-cut relationship between fluoride content in bone and extracellular fluids. The concentration of fluoride in nails (50% higher in finger than in toenails) and hair appears to be proportional to the exposure over longer periods of time taking into account their growth rate (Czarnowski and Krechniak, 1990;Schamschula et al, 1985;Kono et al, 1990;Whitford et al, 1999b). An additional daily intake of 3.0 mg fluoride over 30 days resulted immediately in a 90% increase of the basal urinary fluoride excretion and three months later in an increase of the fluoride content of fingernails (Whitford et al, 1999b).…”
Section: Biomarkers For Fluoride Exposure and Statusmentioning
confidence: 99%
“…The concentration of fluoride in nails (50% higher in finger than in toenails) and hair appears to be proportional to the exposure over longer periods of time taking into account their growth rate (Czarnowski and Krechniak, 1990;Schamschula et al, 1985;Kono et al, 1990;Whitford et al, 1999b). An additional daily intake of 3.0 mg fluoride over 30 days resulted immediately in a 90% increase of the basal urinary fluoride excretion and three months later in an increase of the fluoride content of fingernails (Whitford et al, 1999b). Subjects living in areas with high fluoride content in water (1.6-3.1 mg/L) had 1.8 and 2.9 times higher fluoride contents in fingernails than subjects from areas with intermediate (0.5-1.1 mg/L) and low (<0.11 mg/L) fluoride content in the water, respectively (Schamschula et al, 1985).…”
Section: Biomarkers For Fluoride Exposure and Statusmentioning
confidence: 99%